(untitled) (International Journal of Physiotherapy, 2022)
Background: Total knee arthroplasty (TKA) is a common surgical procedure for patients with advanced osteoarthritis. This study aimed to assess the effects of using versus not using a fast-track protocol, including a new mobilization device called Flexet. Methods: This is a retrospective comparative study. Two groups were formed with a total of 507 TKA patients. 283 were treated in 2010 with a standard program (S group) and 224 with a fast-track protocol (FT group) in 2016. The variables studied were active knee flexion and extension, length of stay, and time to autonomous gait. Results: Study groups were comparable. The mean time from surgery to autonomous gait was shorter for the FT group (4.43 hours, SD = 2.11) than for the S group (59.95 hours, SD = 16.59) (p < 0.001). Mean stay for the FT group was 2.36 nights (SD = 1.81) and 6.20 nights (SD = 1.52) for the S group (p < 0.001). Mean active flexion at hospital discharge was 89.33º (SD = 7.45) in the FT group versus 84.10º (SD = 9.01) in the S group. The mean active extension was: -5.37º (SD= 2.49) in the FT group versus -8.60º (SD = 3.98) in the S group, (p<0.001). Conclusion: Patients in the FT group showed more significant improvements (i.e., shorter length of stay, shorter time to autonomous gait, and larger active ROM in flexion and extension). However, the exact role of the Flexet device is still to be determined.